3D‐printed, externally‐implanted, bioresorbable airway splints for severe tracheobronchomalacia. (22nd February 2019) - Les, Andrea S.; Ohye, Richard G.; Filbrun, Amy G.; Ghadimi Mahani, Maryam; Flanagan, Colleen L.; Daniels, Rodney C.; Kidwell, Kelley M.; Zopf, David A.; Hollister, Scott J.; Green, Glenn E.
Abstract : Objectives/Hypothesis: To report the clinical safety and efficacy of three‐dimensional (3D)–printed, patient‐specific, bioresorbable airway splints in a cohort of critically ill children with severe tracheobronchomalacia. Study Design: Case series. Methods: From 2012 to 2018, 15 subjects received 29 splints on their trachea, right and/or left mainstem bronchi. The median age at implantation was 8 months (range, 3–25 months). Nine children were female. Five subjects had a history of extracorporeal membrane oxygenation (ECMO), and 11 required continuous sedation, six of whom required paralytics to maintain adequate ventilation. Thirteen were chronically hospitalized, unable to be discharged, and seven were hospitalized their entire lives. At the time of splint implantation, one subject required ECMO, one required positive airway pressure, and 13 subjects were tracheostomy and ventilator dependent, requiring a median positive end‐expiratory pressure (PEEP) of 14 cm H2 O (range, 6–20 cm H2 0). Outcomes collected included level of respiratory support, disposition, and splint‐related complications. Results: At the time of discharge from our institution, at a median of 28 days postimplantation (range, 10–56 days), the subject on ECMO was weaned from extracorporeal support, and the subjects who were ventilated via tracheostomy had a median change in PEEP (discharge–baseline) of −2.5 cm H2 O (range, −15 to 2 cm H2 O, P = .022). At median follow‐up of 8.5 months (range, 0.3–77 months), all but one of the 12 surviving subjects lives at home. Of the 11 survivors who were tracheostomy dependent preoperatively, one is decannulated, one uses a speaking valve, six use a ventilator exclusively at night, and three remain ventilator dependent. Conclusions: This case series demonstrates the initial clinical efficacy of the 3D‐printed bioresorbable airway splint device in a cohort of critically ill children with severe tracheobronchomalacia. Level of Evidence: 4 Laryngoscope, 129:1763–1771, 2019